Chemical composition of some medicinal plant products of indigenous origin - Bhowmik, S; Chowdhury, SD; Kabir, MH; Ali, MA (Bangladesh Veterinarian, 2010)
Chemical compositions of leaves of neem (Azadirachta indica), sajna (Moringa oleifera), arjun (Terminalia arjuna), tulsi (Ocimum sanctum), turmeric (Curcuma longa); rhizomes of ginger (Zingiber officinale) and turmeric; fruits of amla (Emblica officinalis), haritaki (Terminalia chebula), bohera (Terminalia belerica) and bulbs of garlic (Allium sativum) of indigenous origin were determined. Proximate and mineral components [Calcium (Ca), Phosphorus (P), Sodium (Na), Potassium (K), Magnesium (Mg), Copper (Cu), Zinc (Zn), Manganese (Mn)] were determined. Dry matter (DM) varied from 964g/kg in arjun leaves to 892g/kg in tulsi leaves. Sajna leaves were high in protein (240g/kg), whereas haritaki fruits were low (34g/kg). Highest amount of ether extract (EE) was found in turmeric rhizomes and the lowest in amla fruits. The crude fibre (CF) ranged from 134 g/kg in turmeric leaves to 7g/kg in garlic bulbs. Highest amounts of ash were found in tulsi leaves (136g/kg), whereas haritaki had 42g/kg. All the plant products had high Nitrogen Free Extract (NFE) and haritaki ranked the highest. Neem leaves contained the highest amount of Ca and Mg. Fruits had lower amounts of P than other products. K content ranged between 8510 ppm in turmeric leaves and 4190 ppm in arjun leaves. Tulsi leaves contain higher amounts of Na, whereas arjun leaves contained less. Tulsi leaves contain higher amount of Cu and Zn than other plant products. The Mn content ranged from 17 ppm in ginger to 780 ppm in garlic bulbs. Only sajna and neem leaves are considered as fair sources of protein. Such ingredients may be considered as good sources of Ca and Mg. DOI: 10.3329/bvet.v25i1.4616 Bangl. vet. 2008. Vol. 25, No. 1, 32-39